The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00540-008-0736-x
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and workload of full-time anesthesiologists in acute care hospitals in Japan

Abstract: Our results provide a quantitative assessment of the duties of anesthesiologists and show that work stress among anesthesiologists is related to workload and other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Physicians are more at risk for occupational stress than the general population, as seen from a Japanese study, with a work stress score being 114 in 383 anesthesiologists as compared with 100 in average workers [12], or a study in Taiwan [13]. Moreover, the Taiwanese study reported a higher proportion of persons suffering from depression among physicians than in the general population (13.3% vs. 3.7%).…”
Section: Discussionmentioning
confidence: 82%
“…Physicians are more at risk for occupational stress than the general population, as seen from a Japanese study, with a work stress score being 114 in 383 anesthesiologists as compared with 100 in average workers [12], or a study in Taiwan [13]. Moreover, the Taiwanese study reported a higher proportion of persons suffering from depression among physicians than in the general population (13.3% vs. 3.7%).…”
Section: Discussionmentioning
confidence: 82%
“…Shortage and misdistribution of anesthetists is a social problem in many countries leading to workload, job dissatisfaction, and finally burnout [8]. Lack of recognition from management and lack of public and client awareness towards the role of anesthetists and feedback towards anesthesia have been indicated as causes of low job satisfaction [1, 5, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The physician shortage is particularly severe in pediatrics, obstetrics and gynecology, and anesthesiology [11,12], which are specialties that generally comprise a large proportion of female physicians.…”
Section: Introductionmentioning
confidence: 99%